2022
DOI: 10.26442/00403660.2022.02.201368
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a probiotic containing Bifidobacterium longum BB-46 and Enterococcus faecium ENCfa-68 in the treatment of post-infectious irritable bowel syndrome. Prospective randomized comparative study

Abstract: Background. In the treatment of post-infectious irritable bowel syndrome (PI-IBS), the leading role belongs to the normalization of the composition of the intestinal microbiome, the disturbances of which are associated with previous intestinal infections. Aim. To study the effectiveness of the drug Bifiform in the treatment of PI-IBS. Materials and methods. An open, prospective, comparative, randomized study included 62 patients with PI-IBS. The diagnosis was confirmed by the results of clinical, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results affirmed that the probiotic product enhanced clinical symptoms of the disease, reinstated the natural balance of the intestinal microbiota, and alleviated inflammation in the intestinal mucosa. In most patients receiving probiotics, the remission of the disease was achieved at the end of the course of treatment and persisted even 6 months after its termination (Yakovenko et al, 2022). A clinical trial conceptualized by Bamola and collaborators assessed the impact of B. clausii UBBC-07 probiotic strain on gut microbiota and cytokines in IBD patients.…”
Section: Probiotics In Inflammatory Bowel Diseasementioning
confidence: 99%
“…The results affirmed that the probiotic product enhanced clinical symptoms of the disease, reinstated the natural balance of the intestinal microbiota, and alleviated inflammation in the intestinal mucosa. In most patients receiving probiotics, the remission of the disease was achieved at the end of the course of treatment and persisted even 6 months after its termination (Yakovenko et al, 2022). A clinical trial conceptualized by Bamola and collaborators assessed the impact of B. clausii UBBC-07 probiotic strain on gut microbiota and cytokines in IBD patients.…”
Section: Probiotics In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Pooled analysis of combinations of probiotics demonstrated a benefit for this outcome, with VSL#3 ® showing a trend towards benefit [ 107 ]. Another small RCT demonstrated that a combination probiotic, Bifiform (containing Enterococcus faecium and Bifidobacterium longum) , was more effective in treating post-infectious IBS compared to standard complex therapy alone, which included an antispasmodic drug, an antibiotic, and a drug to normalize the consistency of feces [ 108 ].…”
Section: Role Of Prebiotics and Probiotics For Various Gastrointestin...mentioning
confidence: 99%
“…However, when treated with Bifiform ® , a probiotic containing E. faecium ENCfa68, a moderate increase in the level of fecal calprotectin was found in 62.2% of patients with colonic dysbiosis. Most patients in the treatment group showed favorable clinical outcomes such as restoration of the normal composition of intestinal microbiota and normalization of fecal calprotectin content at the end of course therapy and 6 months post-treatment [ 29 ].…”
Section: Probiotic Potential (Efficacy Of Enterococcal Strains)mentioning
confidence: 99%